Legal Awareness Level of Electronic Information and Transaction Law Viewed from Understanding and Legal Attitude Aspects Among Students at SMA Negeri 1 Gianyar - Griyawana, I Wayan Gede; Sidaryanti, Ni Nyoman Asri; Yudana, I Made; Diputra, I Putu Nova; Dewi, Desak Made Putri Pradnyan; Dewi, Desak Nyoman Indah Pradnya; Putra, I Gusti Bagus Satria Pratama (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2026)
The digitalization era has transformed social interactions through social media, particularly among Indonesian youth with 204.7 million internet users. Implementation of the Electronic Information and Transaction Law (UU ITE) faces complex challenges among students as digital natives who exhibit a paradox between high technological capabilities and limited digital legal awareness. This study aims to analyze understanding levels and legal attitudes of students at SMA Negeri 1 Gianyar towards UU ITE and identify factors influencing the